Extension of Kirk-Saliga Fixed Point Theorem in a Metric Space with a Reflexive Digraph - Karim Chaira; Abderrahim Eladraoui; Mustapha Kabil; Samih Lazaiz (International Journal of Mathematics and Mathematical Sciences)
We extend the result of Kirk-Saliga and we generalize Alfuraidan and Khamsi theorem for reflexive graphs. As a consequence, we obtain the ordered version of Caristi’s fixed point theorem. Some concrete examples are given to support the obtained results.